Pilot Study: Human Adipose Tissue Allograft for Fat Pad Defects in Patients With Preulcerative Lesions - Matthew J. Regulski, DPM; Molly C. Saunders, BS; Sharron E. McCulloch, MS; Alla Danilkovitch, PhD (Plastic and Reconstructive Surgery, Global Open)
Background:. Loss or displacement of a fat pad on the foot increases plantar pressure, leading to pain and plantar ulcers. These ulcers, especially in patients with diabetic neuropathy, have high recurrence rates, often resulting in amputations. Standard of care focuses on reducing plantar pressure with shoe padding or orthotic devices, leaving the restoration of the fat pad as an unmet medical need. To address this, a human cryopreserved adipose tissue (hCAT) allograft has been developed to repair adipose tissue defects. Methods:. Scientific characterization of hCAT included assessments of its structural properties, immunogenicity, persistence, and remodeling in both in vitro and in vivo models. The incidence of adverse events and ulcer recurrence was analyzed retrospectively in 12 patients with diabetic neuropathy with preulcerative lesions who received 1.5–3.0 mL subcutaneous hCAT implants in areas with fat pad defects. Results:. When implanted in patients, hCAT remained palpable at the implantation sites, and no ulcerations occurred for an average of 6.4 months (range, 2–10 months). No product-related adverse events have been recorded to date. Long-term follow-up for implanted patients is ongoing. Conclusions:. Use of hCAT seems to be safe and potentially beneficial for managing patients at risk for plantar ulcerations. Further studies are warranted to evaluate hCAT’s potential to manage patients at high risk for plantar ulcer formation.